Cytotoxic and Apoptotic Activities of Vernonia amygdalina Extract in HepG2 Cell Line - Harefa, Herman Syukur; Hasibuan, Poppy Anjelisa Zaitun; Harahap, Urip (Indonesian Journal of Pharmaceutical and Clinical Research, 2022)
Liver cancer is a malignant tumor originating from the development of chronic hepatitis or cirrhosis and is responsible for damage to the shape and function of the liver. The loss of the ability of conventional chemotherapy to inhibit the growth of cancer cells is a major focus in the world. Natural ingredients are the solution to this problem, for example the use of Vernonia amygdalina leaves. Vernonia amygdalina contains flavonoids, cardiac glycosides, and steroids/triterpenoids which are reported to have anticancer properties. This study aims to examined the activity of these plants as anticancer liver through cytotocix and apoptotic activity. Vernonia amygdalina ethanol extract (VAEE), Vernonia amygdalina ethyl acetate extract (VAEAE), and Vernonia amygdalina n-hexane extract (VAHE) were obtained from a multistage maceration process. The extracts were tested for cytotoxic activity by the MTT method on HepG2 cells. VAEAE had the best inhibitory concentration 50 (IC50) value of 19.91 Â± 0.24 Âµg/mL. Apoptosis test was performed using double staining method. Subjective observations were made using a fluorescence microscope. It was seen that Vernonia amygdalina ethyl acetate extract was able to trigger apoptosis in HepG2 cells.